Human biomechanics and injury prevention - Kajzer, Janusz; Tanaka, Eiichi; Yamada, Hiroshi (Springer, 2000)
The role of biomechanics in improving the quality of human life is more important today than ever before. Issues as wide-ranging as injury prevention, physical dysfunction, and functional reinforcement through sports are among the diverse concerns and interests of researchers who focus on the biomechanics of the cells, tissues, organs, and systems of the human body. The papers contained in this volume reflect the broad scope of the work being carried out in the field today. Presented at the 1999 International Human Life Support Biomechanics Symposium in Nagoya, Japan, the reports compiled here provide the most up-to-date information from such areas as traffic safety, impact biomechanics, the biomechanics of biological tissues and cells, orthopedic biomechanics, and welfare engineering - for the ultimate goal of achieving better safety, health, and quality of life